Evaluation of in vitro toxicity of polymeric micelles to human endothelial cells under different conditions. (1st February 2017) - Liu, Fang; Huang, Haikang; Gong, Yu; Li, Juan; Zhang, Xuefei; Cao, Yi
Abstract: Polymeric micelles have been extensively studied in the area of antitumor therapy, and more recently explored as nanocarriers for atherosclerosis. These applications of polymeric micelles in biomedicine will increase their contact with human blood vessels. However, few studies have considered the interactions between polymeric micelles and endothelial cells, especially in a complex system. This study used human umbilical vein endothelial cells (HUVECs) as an in vitro model for endothelial cells to investigate the toxic effects of methoxy-poly(ethylene glycol)-poly(d, l -lactide) (MPEG-PLA) based micelles. In addition, an endoplasmic reticulum stress inducer thapsigargin (TG), and a pro-atherogenic stimulus palmitate (PA), were used to co-expose HUVECs to further mimic the responses of diseased endothelial cells to micelle exposure. Overall, up to 200 μg/mL micelles did not significantly induce cytotoxicity, reactive oxygen species (ROS), release of inflammatory mediators in terms of interleukin 6 (IL-6), IL-8 and soluble vascular cell adhesion molecule 1 (sVCAM-1), or adhesion of THP-1 monocytes to HUVECs. TG and PA significantly induced cytotoxicity and THP-1 adhesion as well as modestly promoted the release of IL-6, but did not affect ROS or release of sVCAM-1 and IL-8. Co-exposure of micelles did not significantly enhance the effects of TG and PA to HUVECs, and ANOVA analysis indicated no interaction between concentrations of micelles and the presence of TG/PA. Taken together, these data indicated that micelles are not toxic to HUVECs under different conditions in vitro . Highlights: Toxicity of micelles to endothelial cells under different conditions was studied in vitro . Micelles did not induced cytotoxicity, oxidative stress or inflammatory response. TG/PA treatment induced cytotoxicity and monocytes adhesion to endothelial cells. Micelles did not further enhance the effects of TG/PA.